The Impact of Migrant Labor Force on Housing Sector’s Efficiency of Iran - Hamid Sepehrdoust (فصلنامه پژوهش‌های اقتصادی ایران, 2012)
Iran has been host to the largest number of migrants in the form of Afghan refugees since 1982. These refugees have been permitted to find jobs in Iranian labour market, particularly in the labour intensive markets like manual jobs and construction activities which could not easily be filled by Iranian workers. The research provides a critical review of the impact of migrated Afghan labourers on the efficiency performance of the construction sector of Iranian economy during the period 2006 – 2009, using data envelopment analysis. Results show that, despite the high costs incurred by Iran as host to more than one million refugees, it also benefited from the presence of Afghans. Statistical analysis shows that there is a significant difference between the efficiency scores of the provinces using more migrant Afghan labour force and those having less concentration of such labourers in construction activities. That means most of the technically efficient states in construction activities have the opportunity to employ Afghan workers, since they used to be a very competitive and flexible labour force with unattractive payment. As a result the repatriation program of the Iranian government on Afghan refugees could be limited because of the low levels of substitution among Afghan and Iranian workers in the field of construction.